Adherence of Bacteroides fragilis in vivo. - Onderdonk, A B (1978)
The ability of the encapsulated species Bacteroides fragilis to adhere to rat peritoneal mesothelium was compared to the adherence of unecapsulated strains of Bacteroides (B. distasonis, B. vulgatus, B. thetaiotaomicron, B. ovatus, and B. "other"). Adherence was assayed by attaching plexiglas plates containing 8-mm holes to the peritoneal mesothelium of anesthetized rats. Cell suspension (0.25 ml) was incubated in each well, after which the suspension was aspirated, and a 4-mm punch biopsy was removed. Viable organisms adhering to the biopsy specimen were enumerated by plate count following washing of the biopsy tissue. It was found that B. fragilis adhered significantly better to mesothelial tissue (10(3.00) colony-forming units per biopsy) than unencapsulated species of Bacteroides (10(1.07) colony-forming units per biopsy). This effect was not due to differential oxygen sensitivity of the various inocula. Immunization of rats with capsular polysaccharide did not demonstrate decrease in the adherence of B. fragilis; however, preincubation of the mesothelium with purified capsular polysaccharide resulted in a substantial reduction in adherence. These results indicate that B. fragilis adheres to rat peritoneal mesothelium better than unencapsulated species and suggests that the capsular polysaccharide of B. fragilis plays some role in this increased adherence.